Online predators, an internet insurgency: a field manual for teaching and parenting in the digital arena - Lee, Jeffrey A. (Rowman & Littlefield, 2020)
Introduction : technology and the role of the stakeholder in a child's life -- Information as a weaponized commodity -- Freedoms of the Internet -- The home is not a democracy, and school safety searches -- Truth and efficiency on the Internet -- Nothing is better than the truth -- Hamsters are rats, and devices are hamsters but still rats -- Methodology of the child predator -- Pictures are priceless -- Basic types of child abuse images and other usages of sexual images -- Instant photography -- Is there a plan? -- Which device should I buy? -- What to expect from law enforcement -- The backspace/delete key and self editing -- Educate the child -- Human trafficking and social media : a case study -- A month in the life of an exploitation investigator -- It's not all bad.